Perbandingan Model Pembelajaran Mata Kuliah Metodologi Penelitian Dalam Meningkatkan Kompetensi Mahasiswa - Ahmad Danu Syaputra; Fitria Fitria; Dheo Rimbano (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2019)
The lack of analytical, critical and creative attitudes occurs because of the mindset of students or their teaching staff. This explanation is the basis for why researchers try to study with the aim of making a Comparative Study Model for Research Methodology Courses in Improving Student Competencies to Arrange Final Projects in PTS (Private Universities) in Lubuklinggau City and Musi Rawas Districts. The research population of 5,604 students spread across well-known private Universities in Lubuklinggau City and Musi Rawas District, researchers took a sample of 1%, with a uniform distribution. The researcher uses the frequency crosstab analysis (cross percentage), for the comparative type the researcher uses the technique of One Sample T Test, Independent Sample T Test, and One Way Anova. Research results (1) There are differences in each PTS in the application of learning models in general; (2) There is no difference in each PTS in the application of specific learning models, both the parametric approach model and the micromorph approach model; (3) There are differences in student competencies in each in terms of physical competence; and (4) There are no differences in student competencies in each in terms of intellectual competence; personal; social; and spiritual.